Exploring teachers’ views on benefits, ethical issues, and challenges in integrating AI tools in Malaysian schools - Govindarajoo, Mallika Vasugi V.; Nair, Subadrah Madhawa; Sekhon, Rishijeet Singh; Wai, Chik Soon; Hoong, Lim Chai; Huat, Tan Boon; Okawa, Toshikazu (Edelweiss Applied Science and Technology, 2025)
This study aims to explore teachers’ perceptions of using artificial intelligence (AI) as a teaching tool in schools. It also examines the benefits and challenges associated with AI implementation in the classroom. Additionally, the research investigates the potential ethical risks involved in using AI and evaluates the effectiveness of current policies or guidelines governing AI usage in educational settings. A narrative literature review was conducted to explore AI ethics in education, synthesizing scholarly works, policy documents, and industry reports to contextualize the ethical challenges faced by teachers when integrating AI into their teaching practices. The study employed a mixed-methods approach, incorporating both quantitative and qualitative data. Quantitative data were obtained from a Google Forms survey completed by 38 teachers, while semi-structured interviews were conducted with four teachers to gain deeper insights into AI integration. Data from the survey were analyzed using descriptive statistics, and the interview responses underwent thematic analysis to identify emerging themes. The findings reveal that AI is a useful tool for enhancing teaching efficiency, particularly in lesson planning, assessment, and differentiated instruction. However, issues such as over-dependence on AI, concerns about accuracy, and accountability in AI-generated results also emerged. Furthermore, there is a lack of formal policies and guidelines for AI use in schools. This study highlights the benefits of AI in teaching and learning but emphasizes the need for clear policies and guidelines to address the ethical challenges associated with using AI as a teaching tool.